Interpersonal Relationships of Nurses with Families of Patients in Emergency Rooms Based on Human Becoming Theory - Moch Bahrudin; Tanty Wulan Dari (Institute of Medico-legal Publications Pvt Ltd, 2021)
The purpose of this research is analyzing the influence of nurse’s interpersonal relationship toward human becoming in patient’s ward. This research uses analytical design with cross sectional approach and involves 40 respondents of all the client that in the ward procedure using simple random sampling technique. Research conducted in the ward installation in General Hospital Bangil, starting from may until July 2018.The independent variable of this researches nurse’s interpersonal relationship while the dependent variable is the uncertainty in ward patient. The results showed that nurse’s interpersonal relationships in the favorable criteria (42.5%) and becoming in the emergency room patient in the moderate high level (50%). Results of regression analysis showed the value of probability (sig.) 0.000 is smaller than the value of alpha (0.05) that mean there is significant influence between nurses’ interpersonal relationship toward uncertainty in ward patients with the model of regression is, becoming(y) = 76.316-2,231 x interpersonal relationship (x). Percentage of the influence of nurses’ interpersonal relationship toward uncertainty is 38,9%. In sum, there is significant influence between nurses’ interpersonal relationship toward uncertainty in perioperative patient’s family with the model of regression is, becoming(y) = 76.316-2,231 x meaning(x).